2020
DOI: 10.21203/rs.3.rs-28464/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Undiagnosed Depression among Hypertensive Individuals in Gaza: A Cross-sectional Survey from Palestine

Abstract: Background The aim of this study was to estimate the prevalence and to determine the associated factors of undiagnosed depression amongst hypertensive patients (HTNP) at primary health care centers (PHCC) in Gaza. Methods A cross-sectional survey was conducted including 538 HTNP as a recruitment phase of a clustered randomized controlled trial. Data were collected through a face to face structured interview and depression status was assessed by Beck's Depression Inventory (BDI-II). Data were analyzed by STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These results support the development and dissemination of integrative care approaches for older adults with hypertension. A Cross-sectional Survey from Palestine (31) reported that the prevalence of undiagnosed clinical depression was 11.6%. In addition, the prevalence of 15.4% was found for mild depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the development and dissemination of integrative care approaches for older adults with hypertension. A Cross-sectional Survey from Palestine (31) reported that the prevalence of undiagnosed clinical depression was 11.6%. In addition, the prevalence of 15.4% was found for mild depression symptoms.…”
Section: Discussionmentioning
confidence: 99%